Susceptibility of Gyropsylla spegazziniana (Lizer & Trelles) (Hemiptera: Psyllidae) to Beauveria bassiana (Bals.) Vuill. - Alves,Luis Francisco Angeli (2013)
Gyropsylla spegazziniana is one of the most prominent pest insects of yerba mate culture in all production regions in Brazil, Argentina and Paraguay. Natural enemies have been recorded on G. spegazziniana nymphs and adults, including the Zoophthora radicans entomopathogenic fungus. Since there are no reports of Beauveria bassiana, the aim of this study was to register its pathogenicity with respect to this insect in a laboratory setting. Yerba mate branches were kept in glass flasks with water and we infested each leaf with 20 newly-emerged nymphs. We prepared three replicates per treatment. We sprayed conidia suspensions (1 × 109 conidia/mL) onto the branches, which we transferred to cages and kept in an acclimatized room (26 ± 1°C, 70 ± 10% of relative humidity (R.H.) with a photophase of 14 hours). We evaluated insect mortality daily, and after five days we observed a high level of pathogenicity due to the presence of the fungus, that could be visually observed on the cadaver. The total mortality varied from 25 to 70% (respectively for Unioeste 4 and CG 716) and the confirmed mortality was 30% for Unioeste 52, revealing the fungus' potential. However, more studies are necessary in order to evaluate the strains of this fungus, as well as other species.